Answer:
R__S__T
RT = RS + ST
6x – 4 = ( 4x – 3) + ST
(6x – 4 ) – ( 4x – 3 ) = ST
(6x – 4 ) +( – 4x + 3 ) = ST
2x – 1 = ST
ST = 2x – 1
RS=ST
4x – 3 = 2x – 1
4x – 2x = – 1 +3
2x = 2
x= 2/2
x =1
ST = 2x – 1 = 2(1) – 1 =2 ‐ 1 = 1
ST = 1
I hope I helped you^_^
Answer:
(x-3)^2
Step-by-step explanation:
y = sqrt(x) +3
To find the inverse , we exchange x and y and then solve for y
Exchange x and y
x = sqrt(y) +3
Now solve for y
Subtract 3 from each side
x-3 = sqrt(y)
Square each side
(x-3)^2 = (sqrt(y))^2
(x-3)^2 = y
The inverse of sqrt(x) +3 is (x-3)^2
Answer:
34.95
Step-by-step explanation:
Look at the person above and give them credit
Based off of my understanding, it doesn’t have a y intercept, so it should just be
y = 30x.
Answer: it’s A
Step-by-step explanation: